Mulheres camponesas: trabalho, terra, direitos e movimentos sociais - Carol Matias Brasileiro (2022)
During the Movement Era, dated between the late 1970s and the 1980s, new social actors emerged in the Brazilian political conjuncture. Among them, rural social movements had retaken the debate on the agrarian question, interrupted by the military coup of 1964. Since then, peasant women have been articulated in autonomous and mixed movements, demanding female participation in popular organizations, the guarantee of social rights and access to land for women and an ecological alternative to agrarian production, in face of the predatory hegemony of agribusiness. In the 1960s, Labor Law was placed in opposition to the radical agrarian reform project put forward by the Peasant Leagues, as it presupposed the proletarianization of peasants. However, during the New Republic (1985-2016), with the agricultural modernization process and the precariousness of work in the countryside, popular movements began to demand the strengthening of labor protections for rural workers. The present research has the general objective of systematizing the political position of rural women in relation to Labor Law. To this end, the following specific objectives are pursued: i) to understand the structural difficulties of political practice made by women, peasants and populars in Brazil; ii) understand the context of the organization of peasant women's social movements during the New Republic; iii) identify how each social movement selected refers to Labor Law; iv) analyze how the sexual division of labor is configured in the countryside; v) characterize the dimensions of female care work in the countryside; and, finally, vi) understand how Labor Law affects the conditions of gender, class and territoriality of peasant women. The research assumes the ecofeminist critique of patriarchal capitalist development as an ethical, political and theoretical framework, attributing protagonism to the collective voice of peasant women. Focusing on studies on social movements and the rural women’s work, the methodological approach starts from the bibliographic research to determine the “state of art” of these topics. Also, documentary research was carried out, compiling the political conjuncture in the New Republic and the claims linked to the Labor Law from four of the main peasant women's movements: the Pastoral Land Commission, the Landless Rural Workers Movement, the Marcha das Margaridas and the Peasant Women's Movement. The results indicate that the recurring labor demands are the critic of the seasonal contract, the fight against contemporary slave labor, the guarantee of freedom of association and, consequently, the right to special retirement for rural women. Labor Law appears as an instrument of resistance that makes it possible to reduce overexploitation and social vulnerabilities in the countryside, although it is not the ultimate ideal of social transformation desired by the movements studied.